Relación productividad académica - categoría de investigador Minciencias en el programa de psicología de una universidad colombiana. - OBISPO-SALAZAR, KELLY JOHANA; WILCHES-VISBAL, JORGE HOMERO (Salud Uninorte)
Objective: To determine if there is a relationship between the number of scientific publications and the category of Minciencias researcher in professors of the psychology program of a public university in the Colombian Caribbean. Materials and methods: Spearman coefficient (rs) was used to estimate the correlation between number of publications and researcher category, both in occasional and permanent teachers. The number of publications and category as of December 2022 was considered. Results: The average production was slightly higher in occasional (17) than in plant (13). The existence of a positive, strong, and significant correlation (rs > 0.8 and p < 0.05) was observed in both types of teacher involvement, although slightly higher in occasional ones. However, productivity in casuals is strongly concentrated in 1 researcher. Conclusion: To have a profuse scientific production contributes positively to being categorized as a Minciencias researcher. However, it is essential to have human resource training products, especially at the master's and doctoral level, to reach the Associate and Senior categories. One perspective is to consider the influence of variables such as degree, years of experience, and number of graduate and postgraduate work.